Calcium Phosphates of Interest Biological Coatings on Titanium Surfaces Modified by an Yb:YAG Laser Beam Irradiation - Santos, Marcio L. dos [UNESP]; Riccardi, Carla dos S. [UNESP]; Filho, Edson de A. [UNESP]; Olyveira, Gabriel M. [UNESP]; Fraga, Alexandre F.; Antonio, Selma G. [UNESP]; Bini, Rafael A.; Guastaldi, Antonio C. [UNESP] (Amer Scientific Publishers, 2015)
Calcium phosphates of interest biological coatings were deposited on titanium surfaces modified by Yb:YAG laser beam irradiation under atmospheric pressure and temperature. The coatings were deposited by biomimetic method using different Simulated Body Fluid (SBF) solutions to obtain the calcium phosphates phases. Titanium surface modified by a laser ablation process were immersed in SBF solutions (pH 7.4) during four days at 37 degrees C under oven-dried condition. The samples were characterized by X-ray diffraction (XRD), Rietveld refinement, Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The FTIR spectra showed bands corresponding to chemical bonds. The resulting phases were confirmed by XRD analysis, including amorphous calcium phosphate (ACP), hydroxyapatite (HA) and B-type hydroxycarbonate apatite (B-HCA) phases. The laser-ablation has been established as an adequate process to titanium surface modifications, allowing potentially applications for dental and orthopedic implants.
Keywords: Titanium; Laser Ablation; Biomimetic Method; Calcium Phosphates; Biomedical Applications